Uncertain Lifetime, Imperfect Insurance Markets and the Valuation of Pension Wealth - Ulph, David; Hemming, Richard (Review of Economic Studies, 1980)
In most of the developed countries provision is now made, by either the state or a private institution, for individuals to provide for themselves a retirement income which is a return on the accumulated value of regular payments made during the working life. Given that for many individuals the discounted present value of expected pension rights is one of the most important components of personal wealth it would seem desirable to include an estimate of the former in any measure of the latter. This will require the discounting of anticipated future payments and receipts at an appropriate rate. In the absence of uncertainty and with perfect capital markets anticipated future payments and receipts would be discounted at the prevailing rate of interest on financial assets. Where the individual's lifetime is of uncertain length but there exist perfect insurance markets of the type considered by Yaari (1965) the appropriate rate of discount would be the actuarially fair rate of interest prevailing on insurance notes. Now whilst the individual is uncertain as to how long he will live it is not the case that individuals are observed trading in actuarially fair insurance notes as suggested by the Yaari model. The aim of this paper is to try and obtain some insight into the appropriate rate of discount to be used in the valuation of pension wealth when insurance markets are less perfect than those described by Yaari.